2020
DOI: 10.3390/w12113122
|View full text |Cite
|
Sign up to set email alerts
|

A Need for Standardized Reporting: A Scoping Review of Bioretention Research 2000–2019

Abstract: Bioretention cells are a type of low-impact development technology that, over the past two decades, have become a critical component of urban stormwater management. Research into bioretention has since proliferated, with disparate aims, intents and metrics used to assess the “performance” of bioretention cells. We conducted a comprehensive, systematic scoping review to answer the question of “How is the field performance of bioretention assessed in the literature?”, with the aim of understanding (1) how is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 123 publications
0
25
0
Order By: Relevance
“…As Spraakman et al (2020) and Zuniga‐Teran et al (2020) note, there is a need for standardization within the design process of GI schemes to ensure alignment with regulatory frameworks, with challenges in design standards reflecting the significant uncertainty around how best to plan, design, implement, and maintain GI (Baptiste et al, 2015; Sinnett et al, 2018). Nevertheless, this may be challenging because the performance of GI is largely site specific and their additional ability to deliver multiple co‐benefits under the “four pillars of SuDS development”—that is, (1) flood risk management; (2) improvement to water quality; (3) the provision of public amenity and aesthetic, and; (4) benefits to biodiversity (Woods‐Ballard et al, 2015)—must also be considered alongside their ability to mitigate high intensity storm events.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Spraakman et al (2020) and Zuniga‐Teran et al (2020) note, there is a need for standardization within the design process of GI schemes to ensure alignment with regulatory frameworks, with challenges in design standards reflecting the significant uncertainty around how best to plan, design, implement, and maintain GI (Baptiste et al, 2015; Sinnett et al, 2018). Nevertheless, this may be challenging because the performance of GI is largely site specific and their additional ability to deliver multiple co‐benefits under the “four pillars of SuDS development”—that is, (1) flood risk management; (2) improvement to water quality; (3) the provision of public amenity and aesthetic, and; (4) benefits to biodiversity (Woods‐Ballard et al, 2015)—must also be considered alongside their ability to mitigate high intensity storm events.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…Please note, case studies are not exhaustive and those presented are aggregated over a variety of scales and functional typologies. Spraakman et al (2020) noted that GI research is predominantly focused in global north countries and literature is largely absent from locations with water stresses in the global south. There is a strong focus on GI research in temperate regions (where flood hazards are increasing the most at the global scale; Slater et al, 2021), especially the United States Eastern Seaboard and Australia, emerging in places with strong policy and research cluster interest, such as China (relating to the Sponge City Program) and Europe…”
Section: Introductionmentioning
confidence: 99%
“…A mature site was defined as being three years or more post-construction, as previous findings have indicated that bioretention media needs more than two years to settle (Spraakman et al 2020b), and that the majority of bioretention research is based on systems that are less than 3 years post-construction (Spraakman et al 2020a). Through research project partners (municipalities, conservation authorities and one consulting firm), 29 sites were identified that met the criteria of three years or more post-construction and with contributing drainage areas that were undisturbed (i.e.…”
Section: Site Selectionmentioning
confidence: 99%
“…The previous surveys of mature bioretention systems represent bioretention systems in temperate climates (Wardynski & Hunt 2012;Kluge et al 2018) and one in continental climate (Asleson et al 2009). Bioretention systems originated and have been largely studied in temperate climate zones (Spraakman et al 2020a), and additional research is needed on their performance in the continental climate zone, which is marked by colder winters and hot-humid summers. This study also reflects guidelines and practices in place in Ontario, Canada, which has different media specifications and planting regimens than in Minnesota, North Carolina or Germany.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantages of LID systems vary depending on the type of LID, location, design, and climate. Vegetated LID systems are living structures that are engineered primarily to treat stormwater quantity rather than quality [23] primarily because the knowledge leading to effective designs for water quantity treatment is far more established than that behind water quality treatment [24]. Once constructed, vegetated LIDs require a maturation wait period before use [25] and phosphorus and nitrogen leaching is possible as vegetation becomes established [26].…”
Section: Introductionmentioning
confidence: 99%